Analysis of Swallow Nest Nitrite Levels and Export Volume Projections: A Statistical Approach to Quality Improvement and Global Market Development - Kusumawati, Anjung; Kurniawan, Muhammad 'Ahdi (Media Kedokteran Hewan, 2024)
The global SARS-CoV-2 pandemic is impacting public health and living systems. Edible Bird's Nest (EBN), one of the variants of Swallow's Nest (SBW), is recognized as a medicinal food. The potential of SBW as a therapeutic agent is gaining attention due to its ability to inhibit viral hemagglutination activity. This study provides information on the prediction of SBW demand in the coming year so that it can contribute to determining Indonesia's SBW export performance. Net weight data (tons) of SBW export time series were obtained for 10 years from 2012 to 2022 in 10 countries, namely: Hong Kong, China, Singapore, USA, Vietnam, Canada, Taiwan, Thailand, Japan, and Cambodia, combined with laboratory examination on nitrite levels conducted at the Surabaya Agricultural Quarantine Center, Indonesia. This study shows the minimum limit on nitrite levels in SBW exports and the need for SBW exports in the next four years. One of the requirements for SBW exports is the minimum limit of nitrite levels. The ARIMA method has been implemented to forecast SBW export demand in 10 countries for the next four years. SBW export demand in the next four years is expected to decline. The findings make a significant contribution as a source of information for decision-makers involved in SBW export activities.